PENGEMBANGAN MULTIMEDIA UNTUK KETERAMPILAN MEMBACA CEPAT (FAST READING)DALAM PEMBELAJARAN BAHASA INGGRIS SISWA KELAS VIII - Haryani, Haryani; Aunurrahman, Aunurrahman; Astuti, Indri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
Abstract This research aims is to develop a medium English language learning, especially the fast reading skill, and the media is designed for developing interactive English learning. Data collection techniques such as questionnaires, observation and interviews. All data were collected and analyzed qualitatively. The results concluded that the design based interactive multimedia are developed in accordance with the existing SK-KD. The teaching materials used in this multimedia, namely: understanding a quick read, the formula calculating the effective speed reading, the benefits of rapid reading, and exercise improves reading speed, the learning scenarios interactive multimedia to read quickly using Powerpoint, Ulead VideoStudio 11, and Microsoft Windows 2010 Ultimate , which has six main buttons, the menu of matter, the exercise menu, menu measure reading speed, navigation aid, learning objectives and menu navigation of the designer. When viewed in terms of appearance, have bright colors and fonts that are simple to evoke the spirit, passion, relaxed, cheerful, representing young people, easy to read and most importantly interesting to student responses inferred category AGREE get the highest score in the thirty participants learners are given written advice columns. Given the means of support has existed in MTs Sirajul Ulum Pontianak like LCD, laptop, sound, screen, and sound, interactive multimedia can be used as a medium of learning that fit, especially with all the students of class VIII can operate the computer, so the use of learning media in the form of multimedia this interactive work flawlessly. The trial results to the student media got the potential effects, and the students enjoy and actively follow the lessons using multimedia. Keywords: Development, English, Fast Reading Skill, Multimedia.